Can Congress control spending? [Proceedings - Proxmire, William; American Enterprise Institute for Public Policy Research (Washington : American Enterprise Institute for Public Policy Research, 1973)
The format of this series is designed to encourage dialogue, that form of human communication that provokes intelligent exchange of ideas rather than harangue.
osc 15/06/17
Loans
Keywords: Public Expenditure; United States